A Study on Psychological Effects of Technology Addiction Positive or Negative - meet, Prajapati; ravi, zulasana; Vidani, Jignesh (Contemporary Journal of Applied Sciences, 2024)
This study investigates the psychological impact of technology addiction, focusing on gender differences in anxiety, perceived connectivity, and mental well-being. The study findings reveal a significant correlation between gender and levels of anxiety when separated from digital devices, suggesting that men and women experience different emotional responses to technology use. The study highlights the paradox of increased connectivity leading to feelings of isolation, prompting a re-examination of how technology impacts social relationships. The implications suggest the need for targeted interventions and educational programs to foster healthier technology habits and improve mental well-being. Future research should explore these dynamics further, taking into account diverse populations and the evolving technology landscape